2011
DOI: 10.1167/iovs.10-6059
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Stability during Binocular Viewing in Patients with Age-Related Macular Degeneration

Abstract: Fixational ocular motor control and visual acuity are driven by the better-seeing eye when patients with AMD and large interocular acuity differences perform the tasks binocularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…Fixation instability was defined by the size of the bivariate contour ellipse area, an area within which 68% of all the x,y coordinates of the approximately 10,000 samples of fixation position that occurred during the 20-second period. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Fixation instability was defined by the size of the bivariate contour ellipse area, an area within which 68% of all the x,y coordinates of the approximately 10,000 samples of fixation position that occurred during the 20-second period. 19 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, we were interested to determine whether there exists a positive correlation between visual acuity and fixation stability. Such a correlation is observed in people with macular disease (Reinhard et al, 2007; Tarita-Nistor, Brent, Steinbach & González, 2011), and there are some recent attempts to test whether such a relationship also exists in amblyopic eyes, with inconsistent results. On one hand, based on the results of 13 adult amblyopes (strabismic [ n = 5], anisometropic [ n = 4] and mixed [ n = 4]), González et al (2012) concluded: “For the amblyopia group, visual acuity and fixation stability did not exhibit significant correlations.” (p. 5391).…”
Section: Introductionmentioning
confidence: 99%
“…However, this may be inappropriate for recordings of movements in eyes with retinal disease affecting both eyes differently [27] , as documented in the present study where fixation stability of the worst eye improved when the best eye was included to allow binocular fixation. Therefore, monocular recordings used to diagnose and predict the treatment effect in one eye should be distinguished from binocular recordings that reflect the patient's visual performance.…”
Section: Discussionmentioning
confidence: 84%